A future-oriented approach to company annual reporting in South Africa: Management views - Elmarie Saenger (South African Journal of Business Management, 1993)
A future-oriented approach to company annual reporting is examined as perceived by selected company managements in South Africa. In the article the focus falls on the managers' opinion of three aspects important to the Issue of future-oriented reporting, namely the need for publishing future-oriented information in company annual reports, the type of information to be disclosed and the manner in which it should be presented in company annual reports, and the need for public accountant auditing of the information. As this type of reporting is relatively new in South Africa, an attempt is made to contribute to a better understanding of the subject and to provide some guidance as to its future development.
Keywords: 650